Challenges for halal certification among small scale producers : the case of poultry processing - Husna, Hashim; Tuan Sidek, T. M.; Hasan, Ahmad; Norma, Md Saad; Haniza, Khalid; Hayatullah, Laluddin (Universiti Malaysia Pahang, 2018)
The present study attempts to discover challenges and impediments of small scale poultry processing operators to implement halal certified practices in their operation. This study is qualitative in nature and involves a total of 50 participants among poultry processing operators operating in Pahang, Selangor and Johor states. It can be concluded that the adoption of Malaysian Halal Certification (MS1500:2009) is a big decision for them because of several challenges among others, compliance costs and worrisome of their inability to be in conformity to the stringent requirements of S1500:2009. This study demonstrates the need for more comprehensive institutional support to accommodate the adoption of Halal Certification among small scale poultry operators.